2015
DOI: 10.1093/ije/dyv081
|View full text |Cite
|
Sign up to set email alerts
|

Maternal body mass index during early pregnancy, gestational weight gain, and risk of autism spectrum disorders: Results from a Swedish total population and discordant sibling study

Abstract: Background: Prenatal environmental factors such as maternal adiposity may influence the risk of offspring autism spectrum disorders (ASD), though current evidence is inconsistent. The objective of this study was to assess the relationship of parental BMI and gestational weight gain (GWG) with risk of offspring ASD in a population-based cohort study using family-based study designs.Methods: The cohort was based in Stockholm County, Sweden, including 333 057 individuals born 1984–2007, of whom 6420 were diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
138
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 108 publications
(155 citation statements)
references
References 57 publications
(67 reference statements)
12
138
1
Order By: Relevance
“…39 The lack of longerterm association is consistent with our current investigations of gross motor development. Apart from these studies, many studies measured cognitive abilities, 7 -9, 11, 12, 17, 20 such as IQ or autism spectrum disorder (ASD), 10,14,19,21 which are difficult to directly compare with our results, as these neurodevelopmental phenotypes were not assessed in this study. We did not observe increased odds of problem-solving domain fails until both paternal and maternal weight were in the obese class II/III categories.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…39 The lack of longerterm association is consistent with our current investigations of gross motor development. Apart from these studies, many studies measured cognitive abilities, 7 -9, 11, 12, 17, 20 such as IQ or autism spectrum disorder (ASD), 10,14,19,21 which are difficult to directly compare with our results, as these neurodevelopmental phenotypes were not assessed in this study. We did not observe increased odds of problem-solving domain fails until both paternal and maternal weight were in the obese class II/III categories.…”
Section: Resultsmentioning
confidence: 96%
“…9, 18 -20 Although maternal obesity has been the primary focus of research, 5 -13 evolving evidence suggests a possible role for paternal obesity. 19,21 In particular, de novo mutations and potential shifts in epigenetic programming in sperm and in placenta increase with paternal BMI. 22 -24 Paternal BMI is also important to explore, as it could demonstrate specificity of associations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Bildt et al (2015) No Yes No (= not described) Domellöf et al (2014) No Yes No (= not described) Fernell et al (2015) Yes Yes The 1st cohort group: Bthe Stockholm Somali group^; the 2nd cohort group based in Gothenburg categorized as (a) Swedish, (b) miscellaneous (non-Scandinavian, South America, East Africa), (c) African/Middle East. Gardner et al (2015) Yes No Maternal country of birth categorized as (a) mother born in Sweden, (b) mother born outside Sweden Idring et al (2015) Yes No Maternal country of birth categorized as (a) mother born in Sweden, (b) mother born outside Sweden with low/high Human Development Index (HDI) Idring et al (2014) Yes Yes Maternal country of birth categorized as (a) mother born in Sweden, (b) mother born in Europe outside Sweden, (c) mother born outside Europe Lee et al (2015) Yes No Maternal country of birth categorized as (a) mother born in Sweden, (b) mother born in Europe outside Sweden, (c) mother born outside Europe Löfkvist et al (2014) Yes Yes Swedish language proficiency Lundström et al (2015b) Yes No No (= not described) McEvilly et al (2015) Yes No No (= not described) Selten et al (2015) Yes No Personal or parental history of migration Törn et al (2015) Yes No No (= not described) Zander et al (2015) Yes Yes Maternal country of origin a Coding based on the results reported by the first author/coder the Swedish Personal Data Act (PUL 1998) did not allow registering sensitive personal information such as race, ethnicity or other culture-related data such as religion. Therefore, the use of geographic area or country of origin as proxy for ethnicity by the researchers shown in this study justifies this approach.…”
Section: Scope Of Reporting Cultural Factorsmentioning
confidence: 99%
“…The re-coding of the full sample of the articles by the first coder revealed that items 1 or 2 scored initially as negative were coded as positive for three studies Gardner et al 2015;Lundström et al 2015a); item 4-from negative to positive for two studies Lundström et al 2014), and item 11-from negative to positive for one study (Domellöf et al 2014). These changes in coding resulted in higher total GAP-REACH scores (Table 6).…”
mentioning
confidence: 99%